ANALISIS DAMPAK PENGGUNAAN GARHADADGET TEP PERKEMBANGAN KARAKTER SESUAI DENGAN PROFIL PELAJAR PANCASILA SISWA KELAS VI DI SD NEGERI 2 SAMBONG - Risky, Annisa (Scholarly Journal of Elementary School, 2025)
This study aims to identify the impact of the use of gadgets on character development in accordance with the Pancasila Student Profile and analyze the efforts made by schools to overcome the impact of gadgets on character development in accordance with the Pancasila Student Profile of grade VI students of SD Negeri 2 Sambong. This research uses a qualitative approach with a descriptive method. Data were collected using interview, observation, and documentation techniques. The results of the study show that the use of gadgets in grade VI students of SD Negeri 2 Sambong has a positive impact on the character development of grade VI students, especially in the dimensions of critical, creative, and independent thinking. However, there are still obstacles in terms of discipline and responsibility. The school has made various efforts, such as supervision, gadget use policies, and cooperation with parents to shape student character in accordance with the Pancasila Student Profile.